Implementation Of Multicultural Islamic Religious Education Learning In Sd Taman Harapan And Sd Bina Budi Mulia Malang City - Syamsul Bahri; Djunaidi Ghony; Hasan Busri (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2023)
Islamic Religious Education (PAI), which is carried out in a rigid, monotonous, dogmatic, doctrinal, and theological-normative manner, tends to produce outputs that are insensitive to pluralism and can even lead to intolerance and radicalism. This study aims to analyze the values of multicultural Islamic religious education, which are used as guidelines in planning, implementing, and evaluating at SD Taman Harapan and SD Bina Budi Mulia, Malang City. This study uses a type of qualitative research with a phenomenological approach. Data collection techniques were carried out through participant observation, in-depth interviews, and documentation. data analysis technique called Cresswell spiral analysis. The results of the study show that the application of Islamic Religious Education (PAI) learning at SD Taman Harapan and SD Bina Budi Mulia is called Multicultural PAI. Because it starts from the internalization of school policies, namely the vision, mission, goals, and school activities and programs, as planning, to implementation and evaluation, based on multicultural values. The multicultural values that guide the application of PAI learning are: 1) the value of togetherness; 2) the value of tolerance; 3) the value of mutual respect or appreciation; 4) the value of sharing and helping each other; 5) the value of non-discrimination; 6) the value of equivalence; 7) the value of forgiveness; 8) the value of peace; 9) democratic values; 10) the value of caring; 11) the value of cooperation; and 12) religious values. Multicultural value integration practices are additive and contributive. The formalistic approach, informal internalization approach, socio-cultural approach, and individual approach are other approaches